2017
DOI: 10.17221/177/2016-swr
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on microbial community structure across orchard soil, cropland soil, and unused soil

Abstract: We examined the effects of three different soil conditions (orchard soil, cropland soil, unused soil) on the functional diversity of soil microbial communities. The results first showed that orchard and cropland land use significantly changed the distribution and diversity of soil microbes, particularly at surface soil layers. The richness index (S) and Shannon diversity index (H) of orchard soil microbes were significantly higher than the indices of the cropland and unused soil treatments in the 0–10 cm soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the present paper, a traditional plating technique and a complex medium, which included the most common sugar present in soil (glucose; Gunina & Kuzyakov, ) and a sodium silicate solution (the second most common element present in soil; Vadkertiová et al, ), was used to find the diversity of yeast species associated with the soil adjacent to five fruit trees of the Rosacae family. The soil samples were collected from the surface down to a maximum depth of 10 cm in which layer the richness and diversity of microbes is greatest (Cheng, Zhao, Lv, Li, & Du, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, a traditional plating technique and a complex medium, which included the most common sugar present in soil (glucose; Gunina & Kuzyakov, ) and a sodium silicate solution (the second most common element present in soil; Vadkertiová et al, ), was used to find the diversity of yeast species associated with the soil adjacent to five fruit trees of the Rosacae family. The soil samples were collected from the surface down to a maximum depth of 10 cm in which layer the richness and diversity of microbes is greatest (Cheng, Zhao, Lv, Li, & Du, ).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial activities have been correlated with soil physico-chemical characteristics [3]. It has been reported that soil microbial community composition and metabolic functions depend on the amount and quality of organic matter which is the major source for the survival and sustenance of the soil biota [4]. Soil respiration in terms of CO 2 efflux, considered as an important functional attribute of metabolism, occurs mainly due to the aerobic decomposition of organic matter [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%